The possibility of using foreign experience in the development of the Moscow transport complex - V. E. Komov; A. E. Sibiryaev (Вестник университета)
The issues of development and regulation of transport infrastructure of Moscow from the point of view of the experience of the world’s megacities have been considered. The advantages and disadvantages of the city transport system of Moscow have been adduced, and the necessity of its improvement has been substantiated. The importance of state regulation in this sphere has been emphasized. Successful foreign experience of the European Union, Japan, New Zealand, China, Singapore, the USA and others megacities in the context of its application in large cities of Russia has been examined.